A proposal for measuring resilience in a risky world - Barrett, Christopher B.; Headey, Derek D. (International Food Policy Research Institute, 2014)
Much of the world’s chronically poor and malnourished population lives in an increasingly volatile world. The dangerous nexus of climate change, rapid population growth, conflict, and economic stagnation has already pushed several poor regions into states of permanent crisis, even as the rest of the world has enjoyed unprecedented progress against poverty. This disturbing state of affairs, along with our expanded knowledge of the intimate interactions between short-term shocks and long-run development, has catalyzed widespread interest in resilience building and in what a resilience framework implies for our understanding of the causes and consequences of acute vulnerability to natural and man-made disasters. We propose that the development community invest in a new multicountry system of sentinel sites to undertake long-term, high-frequency measurement and analysis of individual, household, and community resilience in the world’s most vulnerable regions.